PENENTUAN NILAI AMBANG BATAS UNTUK POTENSI RAWAN BANJIR DARI DATA MTSAT DAN QMORPH (STUDI KASUS: BANJIR BENGAWAN SOLO 2007) - Parwati, Parwati; Suwarsono, Suwarsono; Yulianto, Fajar; Suprapto, Totok (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2008)
The relationship between the cloud top temperature from MTSAT-1R and the rainfall from QMorph data in Bengawan Solo water catchment area have been analyzed in this research. The analysis was done using data during 21 – 30 December, 2007 (00 – 23 UTC) for 240 data sets. The result shows that the cloud top temperature which have been potential to be high rain is around 195° - 235° K, whereas the cloud top temperature is greater than 235° K related to the low rainfall. Meanwhile, there was a logarithmic relationship between the rainfall from QMorph data and the cloud top temperature of MTSAT-1R (infrared 1 channal) with the coefficient correlation 0.78. The threshold of the cloud top temperature for the flash flood in Bengawan Solo is lower than 215° K at least lasting for 4 days. The heavy rainfall which occured intensively could be a triggered for the flood disaster around Bengawan Solo water catchment area.